Photomorphogenesis of wheat sprouts with LED irradiation of different intensities. (August 2020) - Han, T; Astafurova, T; Turanov, S; Burenina, A; Butenkova, A; Surnina, E; Valiev, D
Definition of the growth and development characteristics of plants in varied light conditions is a key factor for the creation of highly efficient light facilities for plant cultivation. Experimental research was conducted using an LED irradiation facility with photosynthetic photon flux densities ranging from 0 to 261 μmol m −2 s −1 and a continuous spectrum with maxima at 445 and 600 nm. Under the maximum photosynthetic photon flux density (261 μmol m −2 s −1 ) wheat germs demonstrated diminishing leaf surface with high values of specific leaf area, enhanced pubescence of ground tissues, increases in the number of stomata on the upper epidermis and palisade, and an increase in the thickness of the leaves as well as an increase in carotenoids but a decrease in the chlorophyll a+b/carotenoids relation. It was revealed that the optimum level of photosynthetic photon flux density for the referred spectrum was in the range from 82 to 100 µmol m −2 s −1, which may enable a reduction of irradiance under specific conditions during early development with no harm to the plants while minimizing energy consumption during cultivation.